Senkt Fußballspielen den Blutdruck? - Schrader, Joachim (DMW - Deutsche Medizinische Wochenschrift, 2019)
Playing football leads to a sustainable improvement of cardiovascular risk factors, especially to a reduction of blood pressure in hypertension. For certain target groups football is more attractive with its team character than individual sports. However, the existing studies are not sufficient for an evidence-based recommendation. Therefore, no medical society explicitly recommends football for lowering blood pressure. Urgent studies are needed to adequately evaluate the value of football as a health sport. This includes a special training program and rules, the involvement of football clubs in these programs, the training of appropriate coaches and the involvement of interested physicians. Football could, with its popularity, motivate more people to exercise and contribute to a sustained reduction in cardiovascular disease.
Keywords: Fußball; Sport; Blutdruck; Trainingsprogramm; 3F-Studie